2016
DOI: 10.21037/qims.2016.11.03
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis-T1ρ voxel based relaxometry of the articular cartilage: a comparison of biochemical patterns in osteoarthritis and anterior cruciate ligament subjects

Abstract: Background: Quantitative MR, including T 1ρ mapping, has been extensively used to probe early biochemical changes in knee articular cartilage of subjects with osteoarthritis (OA) and others at risk for cartilage degeneration, such as those with anterior cruciate ligament (ACL) injury and reconstruction.However, limited studies have been performed aimed to assess the spatial location and patterns of T 1ρ . In this study we used a novel voxel-based relaxometry (VBR) technique coupled with principal component ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In contrast, in this study, we applied automated feature learning of CNN in addition to the classical feature extraction techniques, which allowed us to gain the understanding of the relaxation time features. The PCA-based pattern analysis approach applied in this study provided insights on the role of the different layers of cartilage T 2 in characterizing OA; similar results were previously observed in a much smaller pilot study on a separate dataset (N ¼ 40) 29 . Our results suggest that, in addition to the expected global average T 2 prolongation, OA subjects show a localized prolongation just in the deep layer of the cartilage which ultimately results in the T 2 differences between the two layers being different in subjects with radiographic OA compared to controls.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, in this study, we applied automated feature learning of CNN in addition to the classical feature extraction techniques, which allowed us to gain the understanding of the relaxation time features. The PCA-based pattern analysis approach applied in this study provided insights on the role of the different layers of cartilage T 2 in characterizing OA; similar results were previously observed in a much smaller pilot study on a separate dataset (N ¼ 40) 29 . Our results suggest that, in addition to the expected global average T 2 prolongation, OA subjects show a localized prolongation just in the deep layer of the cartilage which ultimately results in the T 2 differences between the two layers being different in subjects with radiographic OA compared to controls.…”
Section: Discussionsupporting
confidence: 76%
“…Forty-seven studies were included in the meta-analysis, including data from 3079 participants. Articles included in the systematic review but excluded from the meta-analysis either examined incomparable regions of interest (ROI), or had insufficient data to be included in the meta-analyses [54, 66, 68, 69, 77, 85, 89, 90].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We limited this initial study to the T 2 analysis of average values across compartments, however, previous studies reported that spatial assessment of the knee cartilage relaxation times using laminar and sub-compartmental analyses could lead to better and probably earlier identification of cartilage matrix abnormalities 36,37 Extraction of second-order statistical information or texture analysis 38,39 has been widely used to overcome the limitation of the average-based approaches. Voxelbased relaxometry techniques have also been previously proposed 40 ; this technique allows for the investigation of local cartilage composition differences, through voxel-based statistics as statistical parametric mapping, 41 principal component analysis, 42 or deep learning feature extractions. 34 TKR is the most effective intervention for end-stage OA 12 ;…”
Section: T 2 Values and Tkrmentioning
confidence: 99%